Death penalty as deterrence for crimes / Hasmahani Hassan Hadeli, Imi Safwani Ismail and Karmuni Abdul Kadir - Hassan Hadeli, Hasmahani; Ismail, Imi Safwani; Abdul Kadir, Karmuni (2006)
The first established death penalty laws dated as far back as the 18th century B.C in the Code of King Hammurrabbi of Babylon, which codified the death penalty for 25 different crimes. The death penalty was also part of the 14th century B.C'S Hittite Code, the 7th century B.C's Draconian Code of Athens, which made death penalty the only punishment for all crimes, and the 15th century B.C's Roman Law of the 12 Tables. Death sentences were carried out by such means as crucifixion, drowning, beating to death, burning alive and implement. In Malaysia, where death penalty is mandatory for a considerable number of offences, the court are left to wring their hands and pass the sentence of death irrespective of the existence of mitigating or extenuating circumstances in the case. The prerogative of mercy lies with the Pardon Boards in the states and to the King in Federal Territories of Kuala Lumpur and Labuan. In the case of Sim Kie Chon v Superintendent of Pudu Prison & Ors2, it was held that royal prerogative of mercy cannot be varied of confirmed by the courts, there being no jurisdiction to do so. The appellant in this case contended that in the case of Datuk Mokhtar Hashim, Pardon Boards had acted unconstitutionally contrary to article 8 (l)3 of the Federal Constitution when the sentenced death commuted to life imprisonment.